Pore-water dissolved inorganic carbon (DIC) and its stable carbon isotopic composition (δ13C) for sediment cores taken during RV Heincke cruise HE575 and HE595 in the Helgoland Mud Area, German Bight - Daniel Müller; Ingrid Dohrmann; Denise Bethke; Heidi Taubner; Kai-Uwe Hinrichs; Sabine Kasten (PANGAEA, 2024)
This dataset includes downcore measurements of dissolved inorganic carbon (DIC) and its stable carbon isotopic composition (δ13C-DIC) for sediment cores retrieved using multi-corer sampling during RV Heincke expeditions HE575 and HE595 in 2021 and 2022 respectively. The samples were collected in the framework of the Project APOC (Anthropogenic impacts on particulate organic carbon cycling in the North Sea). DIC contents were determined in the laboratories of the Alfred Wegener Institute (AWI) in Bremerhaven, Germany. The δ13C-DIC data were produced at MARUM—Center for Marine Environmental Sciences, University of Bremen, Bremen, Germany.